2014
DOI: 10.18085/llas.6.1.r7r784l21q076452
|View full text |Cite
|
Sign up to set email alerts
|

Serenity and Its Relationship to Prosocial and Aggressive Behaviors in Argentinean Children

Abstract: Serenity has been defined as a positive emotion that reflects feelings of inner peace and confidence. The development of serenity constitutes a valuable resource that enables children to cope with life stressors and to establish positive relationships with others. The present study examined serenity and possible gender group differences in Argentinean children. The second goal was to investigate the relation between serenity and prosocial and aggressive behaviors. Participants were 615 children aged 9 to 13 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
5
0
4
Order By: Relevance
“…However, the evidence is less consistent with respect to serenity. Oros found that girls scored higher on this factor while Cuello and Oros ( 2012 ) found similar levels of serenity in boys and girls. These inconsistencies might be due to age disparities in the study samples (7-to 11-year-olds and 9-to 13-year-olds, respectively) or to methodological differences.…”
Section: Gender Differencesmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the evidence is less consistent with respect to serenity. Oros found that girls scored higher on this factor while Cuello and Oros ( 2012 ) found similar levels of serenity in boys and girls. These inconsistencies might be due to age disparities in the study samples (7-to 11-year-olds and 9-to 13-year-olds, respectively) or to methodological differences.…”
Section: Gender Differencesmentioning
confidence: 89%
“…Cuello and Oros ( 2012 ) examined the infl uence of this emotion on prosocial and aggressive behaviors in 9-to 13-year-old children. They found that serenity was associated with prosocial behaviors.…”
Section: Positive Emotions and Social Behaviorsmentioning
confidence: 99%
“…Por último, en relación con la tranquilidad, también se encontró una leve relación con las conductas prosociales en adolescentes, tal como muestran investigaciones previas en niños (Cuello & Oros, 2014). Estas autoras sugieren que altos niveles de serenidad facilitan el desarrollo de las conductas prosociales en los chicos, manifestándose en acciones como confortar a alguien que está triste, ayudar a un compañero de clase a hacer la tarea, compartir dulces con otros, acompañar a sus amigos, etc.…”
Section: Conclusiones Generalesunclassified
“…Estas autoras sugieren que altos niveles de serenidad facilitan el desarrollo de las conductas prosociales en los chicos, manifestándose en acciones como confortar a alguien que está triste, ayudar a un compañero de clase a hacer la tarea, compartir dulces con otros, acompañar a sus amigos, etc. Esto puede deberse a que la serenidad amplía el alcance de la atención, lo que los lleva a poder descubrir las necesidades de los otros (Cuello & Oros, 2014;Fredrickson & Branigan, 2005).…”
Section: Conclusiones Generalesunclassified
“…Específicamente en la etapa de la niñez y adolescencia se ha encontrado que la alegría y la simpatía protegen del rechazo de los pares; que la simpatía y la serenidad facilitan las respuestas asertivas y prosociales, mientras disminuyen las conductas agresivas; que la gratitud también se relaciona negativamente con la agresividad, y que junto con la satisfacción personal y la serenidad, predice un manejo exitoso de los conflictos interpersonales (Cuello & Oros, 2014;de la Vega & Oros, 2013;Giqueaux & Oros, 2008;Lemos, Hendrie & Oros, 2013;Oros, 2008;Richaud de Minzi & Oros, 2009).…”
Section: Introductionunclassified